Preparation and application of confinement type Fenton-like catalytic material for efficiently mineralizing and removing perfluorinated compounds in water
By using Co-MXenes and alumina ceramic sphere composite catalyst in water to activate the persulfate, free radicals are generated to defluoride and degradation of perfluoro compounds, the problem of low removal efficiency of perfluoro compounds in the prior art is solved, and efficient and economical mineralization removal effect is achieved.
Patent Information
- Application Number
- CN202411796583.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art is difficult to effectively remove perfluoro compounds from water, and the traditional treatment methods consume high energy and are inefficient, and it is difficult to achieve complete removal of perfluoro compounds.
Co-MXenes and alumina ceramic sphere composite catalyst are used to activate persulfate through a nano-domain environment to generate free radicals for defluorination and degradation of perfluorinated compounds in water.
It realizes high-efficiency mineralization removal of perfluoro compounds, reduces treatment costs, and avoids the dependence of added energy. It is suitable for the removal of perfluoro compounds in complex wastewater.
Smart Images

Figure CN119608207A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic pollutant degradation, and more specifically, relates to the preparation and application of a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water, wherein Co single atoms are anchored in the confined environment of the nanolayer of MXenes to activate persulfate to produce and Free radicals are used for defluorination and degradation of perfluorinated pollutants in water. Background Art
[0002] Perfluorinated compounds are widely used in various consumer products and industrial production due to their oil-proof, water-proof, high-temperature resistance and extremely high chemical stability. However, they are highly toxic, persistent and bioaccumulative. They enter the environment in large quantities with industrial wastewater discharge, causing lasting damage to humans and the ecological environment. Currently, due to the lack of standards to limit the emission of perfluorinated compound pollutants, most industrial wastewater treatment plans do not have facilities designed to eliminate perfluorinated compounds. Therefore, after industrial wastewater treatment plants, only a small part of perfluorinated compounds (up to 15%) can be removed (mainly through physical and biological adsorption), and the removed part will soon be released back to the wastewater treatment plant or the environment, followed by treatment steps such as media filter backwashing and sludge application. At the same time, more and more perfluorinated intermediates have been found in the discharge of wastewater treatment plants after conventional treatment processes, making it difficult to achieve complete removal of perfluorinated compounds. Therefore, the ideal treatment method is to develop chemical treatment technology to deeply remove perfluorinated pollutants and achieve decomposition and mineralization.
[0003] Due to the strength of the CF bond, perfluorinated compounds are difficult to destroy with most oxidants used in water treatment. Although advanced oxidation technology (AOP) can decompose some perfluorinated compounds, the direct oxidation process is energy-intensive and inefficient. Zhang et al. revealed in "Oxidation of Per-and Polyfluoroalkyl Ether Acids and Other Per-and Polyfluoroalkyl Substances by Sulfate and Hydroxyl Radicals: Kinetic Insights from Experiments and Models" that most perfluorinated compounds react with free radicals with a secondary rate constant of no more than 10 5 M -1 s -1. At present, the pretreatment mode of "reduction and defluorination" of perfluorinated pollutants can accelerate and improve the subsequent AOP treatment effect, and the development of corresponding treatment technology has become a hot research direction in recent years. For example, Liu et al. used the thermal activation of persulfate combined with UV-sulfite reduction in "Near-Quantitative Defluorination of Perfluorinated and Fluorotelomer Carboxylates and Sulfonates with Integrated Oxidation and Reduction" to achieve the defluorination and degradation of most perfluorinated compounds. Nevertheless, since the currently reported treatment methods rely on the catalytic reaction process of external light, heat or electrical energy, they have strict requirements on the structure of the reactor, water quality conditions, operating parameters and other aspects, have high operating costs and difficult maintenance, and do not yet have the conditions for large-scale application.
[0004] Fenton-like water treatment technology is the preferred technology for dealing with high-load and difficult-to-degrade organic pollutants in current industrial wastewater treatment. Among them, the persulfate-based Fenton-like process has many advantages over the traditional Fenton technology, such as high reaction intensity, suitability for neutral pH, and easy storage / transportation / dosage of reagents, and is of great development and application value. Compared with traditional oxidation systems, catalytic reactions occurring under spatial confinement can change the physicochemical properties of free radicals (including coordinated water environment, ability to gain and lose electrons, mass transfer efficiency, etc.), thereby affecting the kinetics and thermodynamic properties of the reaction; in the article "Subnanoscale spatially confined heterogeneous Fenton reaction enables mineralization of perfluorooctanoic acid", the FeOCl confined reaction layer designed by Zhang et al. can enhance the reduction function of superoxide radicals and be used for dehalogenation.
[0005] Therefore, the present invention utilizes the special effect of nano-confinement to regulate the reduction and defluorination function. Free radicals and those with oxidative decomposition function The two work together to achieve the special effect of mineralizing and treating various perfluorinated compound pollutants in industrial wastewater. Summary of the invention
[0006] In view of the above problems, the purpose of the present invention is to provide a preparation and application of a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water. The prepared Co-MXenes and alumina ceramic ball composite catalyst can be loaded in a Fenton-like bed reaction layer, and a confined environment is constructed by the MXenes interlayer spacing to activate the production of persulfate. and It can be used for defluorination and removal of perfluorinated compound pollutants in water bodies.
[0007] The technical solution of the present invention:
[0008] A method for preparing a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water comprises the following steps:
[0009] (1) Under magnetic stirring, lithium fluoride is dissolved in concentrated hydrochloric acid to form a uniform solution; under heating and stirring conditions, titanium aluminum carbide powder is gradually added to the uniform solution, and after etching for 24 hours to remove the Al layer in the titanium aluminum carbide, the solid residue is washed several times with distilled water; finally, the mixed solution is centrifuged and ultrasonically treated in an ice bath under an argon atmosphere to obtain a multilayer two-dimensional MXenes sheet suspension;
[0010] (2) Under magnetic stirring, a multilayer two-dimensional MXenes sheet suspension is dispersed in distilled water to form a uniform dispersion of MXenes; then the uniform dispersion of MXenes and the ClCo2-6H2O solution are ultrasonically treated under argon respectively; under stirring conditions, the ClCo2-6H2O solution is slowly added dropwise to the uniform dispersion of MXenes. After sufficient reaction, Co-MXenes are precipitated with acetone for half an hour and collected by centrifugation, and the product is dried under vacuum to obtain Co-MXenes;
[0011] (3) The Co-MXenes and ceramic balls obtained in step 2 are dispersed in ethanol and ball-milled to obtain a composite catalyst of Co-MXenes and alumina ceramic balls, which is a confined Fenton-like catalytic material.
[0012] In step (1), the mass ratio of lithium fluoride to titanium aluminum carbide in concentrated hydrochloric acid is 3:2, the molar concentration of concentrated hydrochloric acid is 12M, the concentration of lithium fluoride in concentrated hydrochloric acid is controlled to be 100 g / L, and the ultrasonic time is 30 minutes.
[0013] In step (2), the molar concentration ratio of the multilayer two-dimensional MXenes sheet to ClCo2-6H2O in the reaction system is 5:(3-6).
[0014] In step (3), the mass ratio of Co-MXenes to alumina ceramic balls is 1:(5-10), wherein the ball milling condition of Co-MXenes is 500 rpm for 2-3 hours.
[0015] The application of the above confined Fenton-like catalytic material in the oxidation and degradation of perfluorinated compound pollutants in water bodies is as follows:
[0016] Under stirring conditions, Co-MXenes and alumina ceramic ball composite catalyst and persulfate are added to the perfluorinated pollutant wastewater to be treated. The control conditions are: normal pressure, reaction temperature of 20-30°C; the input ratio of catalyst and persulfate in the reaction system is (2-6): (0.15-0.3), and the reaction is carried out at a rotation speed of 400rpm-500rpm for 1-6 hours to degrade the perfluorinated pollutants in the water.
[0017] The perfluorinated pollutant is perfluorooctanoic acid.
[0018] The persulfate is potassium peroxymonosulfate (PMS).
[0019] Working principle of the invention: The invention provides a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water, including a carrier and single-atom Co-MXenes loaded on the carrier; the carrier is an alumina ceramic ball; the mass of MXenes-Co is 6.4% of the mass of the carrier, wherein the multilayer MXenes sheet provides a confined reaction space of 1.5nm. When free radicals are generated in the confined interlayer, their hydration state is destroyed, the hydration coordination energy gap is lower, and they are transformed into The energy barrier is increased, so SO5 can remain in solution and remain sufficiently reactive. After contacting with the CF bond at the head end of perfluorooctanoic acid, H / F exchange occurs, and then the carboxyl group formed by carboxylation is oxidized and removed by sulfate radicals. and The alternating effects achieve defluorination degradation and deep mineralization of perfluorinated pollutants.
[0020] The beneficial effects of the present invention are: a confined Fenton-like catalytic material for high-efficiency mineralization and removal of perfluorinated compounds in water. The preparation process of the confined single-atom Co-MXenes material is simple, and the amount of ClCo2-6H2O can be adjusted to achieve the loading amount of single-atom Co. At the same time, the confined single-atom material can retain the persulfate when activating free radicals, which enable them to react with perfluorinated compounds to defluorinate, allowing The oxidation of perfluorinated compounds is more efficient. In addition, the nano-confined space of MXenes can shield the interference of organic macromolecules in the water environment, and still maintain efficient mineralization ability for perfluorinated compounds in complex wastewater. The above process does not require external energy, and realizes reduction defluorination and oxidation removal in one system, which has profound reference significance for the treatment of wastewater containing perfluorinated pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 yes Figure 6The X-ray absorption near edge structure (XANES) spectrum and extended X-ray absorption fine structure spectrum (EXAFS) spectrum of Co-MXenes-1 prepared in Example 1; wherein a is the XANES spectrum of Co-MXenes-1, and b is the EXAFS spectrum of Co-MXenes-1;
[0022] Figure 2 is the X-ray diffractometer diagram (XRD) of the catalyst prepared in Example 1 of the present invention and Comparative Example 1;
[0023] Figure 3 The scanning electron microscope images and transmission electron microscope images of the Co-MXenes and alumina ceramic ball composite catalysts prepared in Example 1 of the present invention and Comparative Example 1; wherein a is a scanning electron microscope image of Co-MXenes-1, and b is a transmission electron microscope image of S / Co-MXenes;
[0024] Figure 4 The electron paramagnetic resonance spectra of Co-MXenes-1 and S / Co-MXenes catalyst activated persulfate prepared in Example 1 of the present invention and Comparative Example 1 and the liquid phase retention diagram of hydroxyl radical probe terephthalic acid; wherein a is a free radical electron paramagnetic resonance spectrum, and b is a liquid phase product signal retention diagram after terephthalic acid (TPA) reaction;
[0025] Figure 5 1 is a degradation effect diagram of Co-MXenes-1 and S / Co-MXenes catalysts prepared in Example 1 of the present invention and Comparative Example 1 to activate persulfuric acid to remove diphenylamine in 1-hexanol and benzoic acid in aqueous solution; wherein a is a degradation effect diagram for removing diphenylamine (DPA) from 1-hexanol, and b is a degradation effect diagram for removing benzoic acid (BA) in aqueous solution;
[0026] Figure 6 The removal curves and defluorination curves of perfluorooctanoic acid degradation by persulfate activated by Co-MXenes-1, Co-MXenes-2, Co-MXenes-3 and S / Co-MXenes catalyst prepared in Examples 1, 2, 3 and Comparative Example 1 of the present invention; wherein a is the removal curve of perfluorooctanoic acid, and b is the defluorination rate of perfluorooctanoic acid.
[0027] Figure 7 1 is the removal curve and mineralization curve of three representative perfluorinated compounds degraded by activated persulfate in Example 1 of the present invention. Wherein, a is the removal curve of a representative perfluorinated compound, and b is the total organic carbon (TOC) removal rate and defluorination rate of a representative perfluorinated compound. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0029] Example 1
[0030] A method for preparing a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water comprises the following steps:
[0031] (1) Under magnetic stirring, 1.5 g of lithium fluoride was dissolved in 15 mL of concentrated hydrochloric acid. After a uniform solution was formed, 1 g of titanium aluminum carbide powder was gradually added and mixed with the solution. Under magnetic stirring, the solution was heated and stirred. The resulting solid residue was washed several times with distilled water. Finally, the mixed solution was centrifuged and ultrasonically treated in an ice bath under an argon atmosphere for 30 minutes to obtain a multilayer two-dimensional MXenes sheet.
[0032] (2) A 2 g / L MXene suspension was dispersed in 50 mL of distilled water under magnetic stirring to form a clear solution. The MXene suspension and 50 mL of 7 mM ClCo2-6H2O were then ultrasonically treated under argon for 30 min. The ClCo2-6H2O solution was slowly added dropwise to the MXene under stirring. After sufficient reaction, Co-MXenes were precipitated with acetone for half an hour and collected by centrifugation, and the product was dried under vacuum.
[0033] (3) 0.25 g of Co-MXenes and 2.5 g of ceramic balls in step (2) were dispersed in 50 mL of ethanol and ball-milled at 500 rpm for 2 hours to obtain a composite catalyst of Co-MXenes and alumina ceramic balls, i.e., a catalytic material. The proportion of single-atom Co in MXene is 6.8%, recorded as Co-MXenes-1.
[0034] Furthermore, the reactor containing the wastewater to be treated is placed on a stirring table, and the Co-MXenes and alumina ceramic ball composite catalyst and persulfate prepared in step (3) are added into the wastewater. The control conditions are: normal pressure, reaction temperature of 20-30°C; the amount of the MnO2 nanotube and alumina ceramic ball composite material prepared in step 4 in the reaction system is 6 g / L, the concentration of persulfate in the reaction system is 1 mM, and the reaction is carried out at a rotation speed of 400 rpm for 5 hours to oxidize and degrade organic pollutants in the water.
[0035] Example 2
[0036] This embodiment differs from Specific Example 1 in that the concentration of ClCo2-6H2O in step (2) is controlled to be 5 mM, and a catalytic material in which Co-MXene accounts for 5.3% in the ceramic ball is obtained, which is recorded as Co-MXenes-2. The rest is the same as Specific Example 1.
[0037] Example 3
[0038] This embodiment differs from Specific Example 1 in that the concentration of ClCo2-6H2O in step (2) is controlled to be 3 mM, and a catalytic material in which Co-MXene accounts for 3.8% in the ceramic ball is obtained, which is recorded as Co-MXenes-3. The rest is the same as Specific Example 1.
[0039] Example 4
[0040] The difference between this embodiment and Specific Example 1 is that the ball milling time in step (3) is controlled to be 3 hours, and the catalytic material in which the proportion of Co-MXene in the ceramic ball is 8.9% is obtained, which is recorded as Co-MXenes-4. The rest is the same as Specific Example 1.
[0041] Example 5
[0042] The difference between this embodiment and specific example 1 is that in step (3), the dosage of Co-MXenes and ceramic balls is controlled to be 0.25 g and 1.25, respectively, to obtain a catalytic material in which Co-MXene accounts for 5.6% of the ceramic balls, which is recorded as Co-MXenes-5. The rest is the same as specific example 1.
[0043] Example 6
[0044] The difference between this embodiment and specific example 1 is that in step (3), the dosage of Co-MXenes and ceramic balls is controlled to be 0.25 g and 1.75, and a catalytic material in which Co-MXene accounts for 5.9% of the ceramic balls is obtained, which is recorded as Co-MXenes-6. The rest is the same as specific example 1.
[0045] Comparative Example 1
[0046] A method for preparing a non-confined Fenton-like catalytic material for treating perfluorinated compounds in water comprises the following steps:
[0047] The difference between this embodiment and specific embodiment 1 is that the Co-MXenes dispersion obtained in step (2) is continuously stirred at 35°C for 30 minutes, then ultrasonically treated in an ice bath under an argon atmosphere for 2 hours, and centrifuged at 6000 rpm for 20 minutes. The above process is repeated for 3 cycles and freeze-dried to obtain a single-layer Co-MXene, recorded as S / Co-MXenes, and the rest is the same as specific embodiment 1.
[0048] The present invention is verified by the following tests:
[0049] Experiment 1: This experiment is to detect the active substances produced by persulfate activation of Co-MXenes and S / Co-MXenes catalysts. Take 1mL of 2mM PMS mother solution prepared with deionized water and add it to 100mL of perfluorooctanoic acid solution prepared with deionized water, so that the concentration of perfluorooctanoic acid and PMS in the solution are 0.02mM and 1mM, respectively, and mix thoroughly at 400rpm in a mechanical stirrer. After adding 200mg of catalyst, start timing, take samples after 5 minutes of reaction, and then pass through a 0.22μm PES polyethersulfone membrane. Take 1mL of the filtered sample and place it in a centrifuge tube. 2,2,6,6-tetramethyl-4-piperidinol (TEMP, >99%) is dissolved in a phosphate buffer solution (pH=7.4) with a final concentration of 50mM. Then, TEMP solution (40μL) is mixed with the extracted 40μL filtered sample. The mixed solution of TEMP is absorbed by a quartz capillary and the signal corresponding to singlet oxygen is detected from the spin-trapped adduct in EPR. The signal of singlet oxygen in EPR is as follows: Figure 4 As shown in a.
[0050] Experiment 2: This experiment is to detect the persulfate-specific probe experiment for the activation of Co-MXenes and S / Co-MXenes catalysts. The probe (TPA, BA and DPA) concentration and PMS concentration were configured to be 0.05mM and 0.5mM respectively, and fully mixed at 400rpm in a mechanical stirrer. After adding 200mg of catalyst, the timing was started, and samples were taken at intervals within 5 minutes. After passing through a 0.22μm PES polyethersulfone membrane, 1mL of the filtered sample was taken and placed in a centrifuge tube. TBA and BA were detected by high performance liquid chromatography, and DPA was detected by UV-visible analyzer.
[0051] Experiment 3: This experiment is to activate the designed catalyst to remove perfluorinated pollutants in persulfate water, and compare the removal effects of confined catalysts with different single-atom contents (Co-MXenes-1, Co-MXenes-2 and Co-MXenes-3) and non-confined S / Co-MXenes on perfluorinated pollutants. 0.5 mL of 100 mM PMS mother solution prepared with deionized water was added to 100 mL of perfluorooctanoic acid solution prepared with deionized water, so that the concentration of perfluorooctanoic acid and PMS in the solution were 0.02 mM and 1 mM respectively, and the mixture was fully mixed at 400 rpm in a mechanical stirrer. After adding 200 mg of catalyst, the timing was started, and sampling was performed at different sampling times. After passing through a 0.22 μm PES polyethersulfone membrane, 1 mL of the filtered sample was placed in a centrifuge tube, and 0.5 mL of 10 mmol / L sodium thiosulfate was added to quench the sample. The sample was stored at low temperature (4 ° C) and the concentration of perfluorinated pollutants at different sampling times was determined by high performance liquid chromatography-mass spectrometry; the removal of fluoride ions and total organic carbon in the reaction was detected by ion chromatography and total organic carbon analyzer. The corresponding results are shown in Figure 2. Figure 6 , 7 shown.
[0052] Figure 1 a is the XANES spectrum of Co-MXenes-1 prepared in Example 1. XANES is used to study the electronic state of Co atoms. The results show that the valence state of Co in Co-MXenes-1 is between Co foil and Co3O4. This indicates that the Co species in Co-MXenes-1 are positively charged. Figure 1 b EXAFS measurement further confirms the chemical structure of Co atoms fixed on MXenes. No Co-Co bonds (present in the Co foil EXAFS spectrum) were detected nearby. There is a main peak at , which is related to the Co-O bonding configuration. The Co-O coordination number is 2.9 and the bond length is The above results clearly show that single-atom Co is successfully anchored in MXenes with Co-O3 coordination.
[0053] Figure 2It is an X-ray diffractometer diagram of the catalyst prepared by Example 1 of the present invention and Comparative Example 1; Co-MXenes nanosheets loaded with Co single atoms. The X-ray diffraction diagrams of MXenes and Co-MXenes show that the interlayer spacing does not change after the introduction of Co single atoms. According to the Bragg equation (2dsinθ=nλ, where θ is the angle between the incident ray, the reflected ray and the reflected crystal plane, λ is the wavelength 0.1542, and n is the reflection order 1), it can be calculated that the interlayer spacing of Co-MXenes and MXenens is 1.5nm. After repeated centrifugal ultrasound, the layered Co-MXenes structure is peeled off, and the 002 characteristic peak in the XRD of the corresponding MXenes almost disappears.
[0054] Figure 3 These are scanning electron microscope images and transmission electron microscope images of the Co-MXenes, S / Co-MXenes and alumina ceramic ball composite catalysts prepared in Example 1 and Comparative Example 1 of the present invention. Figure 3 b shows that the multilayer Co-MXenes are accordion-shaped, and after the multilayer Co-MXenes are peeled off, Figure 3 The single-layer S / Co-MXenes are also clearly shown in b.
[0055] Figure 4 a is the electron paramagnetic resonance spectra of Co-MXenes-1 and S / Co-MXenes catalyst activated persulfate prepared in Example 1 and Comparative Example 1 of the present invention. Both systems show strong mixed peaks of sulfate and hydroxyl radical signals. In order to distinguish specific free radical species, we use terephthalic acid, a specific probe for hydroxyl radicals, as the detection substance. The principle is that hydroxyl reacts with TPA to generate hydroxyterephthalic acid (hTPA), and the addition product can be detected in the liquid phase. Figure 4 b. In order to better illustrate the results, we used the classic Fenton system to produce hydroxyl radicals. The hTPA peak appeared at a liquid retention time of 10 minutes. However, the Co-MXenes-1 and S / Co-MXenes catalysts prepared in the examples and comparative examples could not produce hydroxyl radicals. Combined with the electron paramagnetic resonance results, it was shown that the above catalysts could only activate persulfate to produce sulfate radicals.
[0056] Figure 5 a is the curve of the removal of DPA in 1-hexanol by Co-MXenes-1 and S / Co-MXenes catalysts prepared in Example 1 of the present invention and Comparative Example 1, which can be used to detect the reducibility of PMS produced in the Haber-Weiss cycle Shows sufficient reactivity with aromatic amines, among which The free radicals and OH hydroxyl groups were completely quenched in the organic solvent, and the characteristic signal peak of DPA at UV 285nm disappeared rapidly, indicating that However It is extremely unstable in aqueous solution and will be consumed through various side reactions. Free radicals are easily converted into like Figure 5 b. Benzoic acid (BA) is used as a free radical probe to quantify the free radical concentration in the reaction system. The BA kinetics induced by the S / Co-MXenes catalyst prepared in Comparative Example 1 is significantly better than that of Co-MXenes-1 prepared in Example 1, which indicates that after the confined structure of Co-MXenes-1 is stripped off, Due to the hydration effect, it is quickly converted into Free radicals.
[0057] Figure 6 These are the removal curves and defluorination curves of Co-MXenes-1, Co-MXenes-2, Co-MXenes-3 and S / Co-MXenes catalysts prepared in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1 for the degradation of perfluorooctanoic acid by activating persulfate. The free radicals first undergo H / F exchange with perfluorooctanoic acid, inducing the CF bond to transform into a CH bond, resulting in an unstable perfluorocarbon chain structure. Free radicals are more likely to remove the carboxyl group in perfluorooctanoic acid, and the exposed CH bond is carboxylated in water to form a carboxyl group, which is then Oxidative removal. and The removal of perfluorooctanoic acid is completed by alternating effects. Among them, as the catalyst content in Co-MXenes-1, Co-MXenes-2, and Co-MXenes-3 decreases successively, the efficiency of catalyst activation PMS to remove perfluorooctanoic acid and the defluorination rate also decrease successively. For Co-MXenes-4 prepared in Example 4, although a higher catalyst composite ratio is obtained, the excessively thick accumulation of Co-MXenes on the surface of the ceramic ball affects the mass transfer of the reaction solution, resulting in a worse catalytic performance than the catalyst prepared in Examples 1 and 2 with lower loadings. When the S / Co-MXenes obtained by peeling off the confined structure in the comparative example, due to the generation of Disproportionately hydrated There is no chance to react with PFOA, which is difficult to remove by oxidation alone, even if S / Co-MXenes produces more The corresponding PFOA removal and defluorination rates were also extremely weak.
[0058] Figure 7a is the removal curve of three representative perfluorinated pollutants degraded by activated persulfate in Example 1 of the present invention. The structures of the other two representative perfluorinated compounds selected are perfluorooctane sulfonic acid (PFOS, with sulfonic acid group) and perfluoro-4-methoxybutyric acid (PFMA, with carbonyl and carboxyl groups). Although they are different in structure, they are both removed in the Co-MXenes / PMS oxidation system. and Rapidly eliminated. Figure 7 b, all three perfluorinated pollutants showed extremely high defluorination effects, and the corresponding TOC in the reaction system was also removed. This shows that the confined single-atom catalysis designed by the present invention achieves effective destruction of perfluorinated pollutants under the typical Fenton-like operation, opening up a new path for the future development of advanced catalysts with nano-configured single-atom structures.
Claims
1. A method for preparing a confined Fenton-like catalytic material for high-efficiency mineralization removal of perfluorinated compounds in water, characterized in that: The steps include: (1) Under magnetic stirring, lithium fluoride is dissolved in concentrated hydrochloric acid to form a uniform solution; under heating and stirring conditions, titanium aluminum carbide powder is gradually added to the uniform solution, and after etching for 24 hours to remove the Al layer in the titanium aluminum carbide, the solid residue is washed several times with distilled water; finally, the mixed solution is centrifuged and ultrasonically treated in an ice bath under an argon atmosphere to obtain a multilayer two-dimensional MXenes sheet suspension; (2) Under magnetic stirring, a multilayer two-dimensional MXenes sheet suspension is dispersed in distilled water to form a uniform dispersion of MXenes; then the uniform dispersion of MXenes and the ClCo2-6H2O solution are ultrasonically treated under argon respectively; under stirring conditions, the ClCo2-6H2O solution is slowly added dropwise to the uniform dispersion of MXenes. After sufficient reaction, Co-MXenes are precipitated with acetone for half an hour and collected by centrifugation, and the product is dried under vacuum to obtain Co-MXenes; (3) The Co-MXenes and ceramic balls obtained in step 2 are dispersed in ethanol and ball-milled to obtain a composite catalyst of Co-MXenes and alumina ceramic balls, which is a confined Fenton-like catalytic material.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of lithium fluoride and titanium aluminum carbide in concentrated hydrochloric acid is (2-3): (1-2).
3. The preparation method according to claim 1, characterized in that: In step (1), the molar concentration of concentrated hydrochloric acid is 12M.
4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of lithium fluoride in concentrated hydrochloric acid is controlled to be 100 g / L.
5. The preparation method according to claim 1, characterized in that: In step (1), the ultrasonication time is 30 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: In step (2), the molar concentration ratio of the multilayer two-dimensional MXenes sheet to ClCo2-6H2O in the reaction system is 5:(3-6).
7. The preparation method according to claim 1, characterized in that: In step (1) and step (3), the mass ratio of Co-MXenes to alumina ceramic balls is (1-2):(3-5), wherein the ball milling condition of Co-MXenes is 500 rpm for 2-3 hours.
8. Application of the confined Fenton-like catalytic material obtained by the preparation method according to any one of claims 1 to 7 in oxidative degradation of perfluorinated compound pollutants in water, characterized in that: Here are the steps: Under stirring conditions, Co-MXenes, alumina ceramic ball composite catalyst and persulfate are added to the perfluorinated pollutant wastewater to be treated. The control conditions are: normal pressure, reaction temperature of 20-30°C; the reaction is carried out at a rotation speed of 400rpm-500rpm for 1-6 hours to degrade the perfluorinated pollutants in the water.
9. The use of the method for oxidative degradation of perfluorinated compound pollutants in water according to claim 8, characterized in that: The input ratio of the catalyst to the persulfate in the reaction system is (2-6): (0.15-0.3).
10. The use of the method for oxidative degradation of perfluorinated compound pollutants in water according to claim 8, characterized in that: The perfluorinated pollutant is perfluorooctanoic acid, and the persulfate is potassium peroxymonosulfate.
Citation Information
Patent Citations
Sandwich-shaped Co3O4@Mxenes composite material and preparation method and application thereof
CN113559903A
Preparation and application of CoS / Ti3C2 MXene composite material
CN114849748A
Confined-range catalytic membrane material for deep water purification and preparation method of confined-range catalytic membrane material
CN115845851A
Catalytic material taking MXene as carrier to load cobalt and preparation method of catalytic material
CN116265098A
Destruction of Perfluorosulfonic Acids (PFSAs) via Supercritical Water Oxidation
US20230373824A1